Actions of pituitary hormones beyond traditional targets. Issue 3 (June 2018) - Zaidi, Mone; New, Maria I; Blair, Harry C; Zallone, Alberta; Baliram, Ramkumarie; Davies, Terry F; Cardozo, Christopher; Iqbal, James; Sun, Li; Rosen, Clifford J; Yuen, Tony
Abstract : Studies over the past decade have challenged the long-held belief that pituitary hormones have singular functions in regulating specific target tissues, including master hormone secretion. Our discovery of the action of thyroid-stimulating hormone (TSH) on bone provided the first glimpse into the non-traditional functions of pituitary hormones. Here we discuss evolving experimental and clinical evidence that growth hormone (GH), follicle-stimulating hormone (FSH), adrenocorticotrophic hormone (ACTH), prolactin, oxytocin and arginine vasopressin (AVP) regulate bone and other target tissues, such as fat. Notably, genetic and pharmacologic FSH suppression increases bone mass and reduces body fat, laying the framework for targeting the FSH axis for treating obesity and osteoporosis simultaneously with a single agent. Certain 'pituitary' hormones, such as TSH and oxytocin, are also expressed in bone cells, providing local paracrine and autocrine networks for the regulation of bone mass. Overall, the continuing identification of new roles for pituitary hormones in biology provides an entirely new layer of physiologic circuitry, while unmasking new therapeutic targets.